Impact of hypoxic versus oxic conditions on local tumor control after proton irradiation in a rat prostate carcinoma - Schmitt, Michaela; Glowa, Christin; Kurth, Ina; Peschke, Peter; Brons, Stephan; Karger, Christian (Clinical and translational radiation oncology, 2025)
Background and purpose - Hypoxia in tumors significantly contributes to radiation resistance, often leading to poor treatment outcomes. In vitro studies demonstrated that proton irradiation not only exhibits an increased relative biological effectiveness (RBE), but also a lower oxygen enhancement ratio (OER). This study explored the impact of hypoxic and oxic conditions on local tumor control after proton irradiation in a rat prostate carcinoma. - Material and methods - Subcutaneously transplanted Dunning R3327-HI rat prostate carcinomas were irradiated with varying single doses of protons under oxic or hypoxic conditions. Hypoxia was induced by clamping the tumor-supplying vessels. The biological endpoint was local tumor control assessed 300 days after irradiation. Dose-response curves were determined and based on the doses required for 50 % tumor control probability (TCD50), the RBE and OER were calculated. - Results - The TCD50 value was significantly higher under hypoxic than under oxic conditions (73.4 ± 1.9 Gy vs. 50.5 ± 1.6 Gy), resulting in an OER of 1.45 ± 0.06 for proton irradiation. Compared to photon irradiation, the RBE for protons was of 1.23 ± 0.07 under oxic and 1.30 ± 0.04 under hypoxic conditions. - Conclusion - Proton irradiations showed a 5 % reduction in OER compared to the previously measured photon value of 1.53 ± 0.08, suggesting a slightly higher effectiveness of protons in hypoxic tumors as compared to photons.
Online veröffentlicht: 12. April 2025, Artikelversion: 17. April 2025
Gesehen am 11.11.2025